Characteristics of an open-cut coal mine fire pollution event. (February 2017) - Reisen, Fabienne; Gillett, Rob; Choi, Jason; Fisher, Gavin; Torre, Paul
Abstract: On 9 February 2014, embers from a nearby grass/shrub fire spotted into an unused part of the Hazelwood open-cut brown coal mine located in the Latrobe Valley of Victoria, Australia and started a fire that spread rapidly and extensively throughout the mine under strong south-westerly winds and burned over a period of 45 days. The close proximity of the town to the coal mine and the low buoyancy of the smoke plume led to the accumulation of dense smoke levels in the township of Morwell (population of 14, 000) particularly under south-westerly winds. A maximum daily PM2.5 concentration of 731 μg m −3 and 8-h CO concentration of 33 ppm were measured at Morwell South, the closest residential area located approximately 500 m from the mine. These concentrations were significantly higher than national air quality standards. Air quality monitoring undertaken in the Latrobe Valley showed that smoke from the Hazelwood mine fire affected a wide area, with particle air quality standards also exceeded in Traralgon (population of 25, 000) located approximately 13 km from the mine. Pollutant levels were significantly elevated in February, decreased in March once the fire abated and then returned to background levels once the fire was declared safe at the end of March. While the smoke extent was of a similar order of magnitude to other major air pollution events worldwide, a closer look at emissions ratios showed that the open combustion of lignite brown coal in the Hazelwood mine was different to open combustion of biomass, including peat. It suggested that the dominant combustion process was char combustion. While particle and carbon monoxide monitoring started approximately 4 days after the fire commenced when smoke levels were very high, targeted monitoring of air toxics only began on 26 February (17 days after the fire) when smoke levels had subsided. Limited research on emission factors from open-cut coal mine fires make it difficult to assess the likely concentrations of air toxics emitted during the initial more intense period of the fire. Highlights: An open-cut coal mine fire burning for 45 days impacted nearby populations of 45, 000. CO, PM2.5 and benzene exceeded air quality standards by up to 30 times. PM to CO emission ratios suggest char combustion as dominant combustion process. Study provides unique data set on emissions from open-cut coal mine fire.